Implikasi Frasa ‘Masih Ada’ Pasal 3 Uupa bagi Pengakuan Masyarakat Adat dan Kebijakan “Ius Constituendum” - Ilham Muhammad Zain; Aab Abdul Jamalul Lael; Khoirul Abdul Aziz; Tevan Agus Setiawan; Exsyel Hendy Basuki; Hezron Sabar Rotua Tinambunan (Jurnal Hukum Lex Generalis, 2026)
The phrase "sepanjang menurut kenyataannya masih ada" in Article 3 of the UUPA creates normative ambiguity that places indigenous peoples in a vulnerable position. This study aims to analyze the juridical implications of the phrase and formulate ius constituendum policies. The discussion results indicate that this phrase is a transitional arrangement resulting in sectoral regulatory fragmentation and complex administrative burdens of proof for indigenous peoples. In conclusion, a paradigm shift from conditional to inherent recognition is required. Future policies must remove the phrase, adopt self-identification principles and harmonize regulations to ensure legal certainty and justice for indigenous peoples.